The motivations of microfinance institutions to enter the housing market in a developing country. Issue 4 (1st October 2020) - Bondinuba, Francis K.; Stephens, Mark; Jones, Colin; Buckley, Robert
Abstract: Microfinance is a potential powerful avenue to support the lowest socioeconomic groups in the housing market of developing countries. The purpose of this article is to consider what motivates microfinance institutions (MFIs) to enter the housing market through a factor analysis approach. A survey of 125 respondents was undertaken in two regions of Ghana. Factor analysis was conducted to identify underlying latent variables that had significant effects on MFIs' decision to enter the housing market. The findings indicate that four important determinants emerge: MFIs' interest for profit, the ease of entry into the housing market, interest for growth, and the perceived desire of the lowest socioeconomic groups for homeownership. The study also implies that some nuances help explain the demand and supply perspectives of housing microfinance in developing countries.